Pathology, Assessment and Treatment of Structures Affected by Delayed Ettringite Formation. Issue 3 (1st August 2017) - Godart, Bruno
Abstract: Expansive internal sulphate reaction of concrete due to delayed ettringite formation (DEF) can damage concrete structures severely. DEF is defined as the formation of ettringite in a concrete after setting, and without any external sulphate supply but with water supply. This phenomenon occurs in concretes exposed to frequent humidity or contact with water, and subjected to a relatively high thermal treatment (>65° C) or having reached high temperatures during casting. This reaction may cause large structural disorders due to unexpected deformations and additional stresses in concrete and reinforcement, and therefore knowledge about how to deal with such structures affected by DEF is essential. After a presentation of the disorders due to DEF and an analysis of their causes based on cases encountered in practice, the paper presents the three steps of the appraisal methodology by developing the assessment based on numerical modelling, and reviews the various treatment solutions that may be implemented to deal with existing affected structures whose serviceability and structural safety may constitute a serious concern.